Prospective cohort studies of beta-trace protein and mortality in haemodialysis patients and patients undergoing coronary angiography. Issue 11 (20th February 2018) - Enko, Dietmar; Meinitzer, Andreas; Scharnagl, Hubert; Stojakovic, Tatjana; Kleber, Marcus E; Delgado, Graciela E; Zelzer, Sieglinde; Drechsler, Christiane; Krämer, Bernhard K; Wanner, Christoph; März, Winfried; Woitas, Rainer P
Abstract: Background: Beta-trace protein (BTP) is a low-molecular-weight glycoprotein, which may serve as an endogenous biomarker of kidney function and cardiovascular risk. Methods: We examined cardiovascular and all-cause mortality according to BTP concentrations in 2962 individuals referred for coronary angiography from the Ludwigshafen Risk and Cardiovascular Health study and in 907 patients with Type 2 diabetes mellitus undergoing haemodialysis from the German Diabetes and Dialysis (4D) study. Results: Haemodialysis patients had considerably higher median (interquartile range) BTP concentrations [6.00 (4.49–7.96) mg/L] and experienced a 4-fold increased mortality rate compared with coronary angiography patients [BTP concentration: 0.55 (0.44–0.67) mg/L]. After adjustment for age, sex, cardiovascular risk factors and creatinine, 4D patients in the highest quartile (>7.96 mg/L) had a 1.6-fold increased rate of all-cause mortality [hazard ratio (HR) 1.62, 95% confidence interval (CI) 1.19–2.20] compared with the lowest quartile (<4.49 mg/L) (P = 0.002) In patients undergoing coronary angiography, the adjusted HRs (95% CI) for all-cause and cardiovascular mortality were 1.23 (1.0–1.51) and 1.27 (0.99–1.63) in the highest (>0.67 mg/L) compared with the lowest (<0.44 mg/L) quartile (P = 0.043 and 0.062). In both cohorts, the BTP/creatinine ratio was a stronger predictor of all-cause and cardiovascular mortality compared with BTP. Conclusion: BTP was associated with all-cause mortality independently of renal function in haemodialysis patients. The BTP/creatinine ratio was more predictive for all-cause and cardiovascular mortality in haemodialysis patients and individuals referred for angiography compared with BTP as single marker.